(3TQM GdebGeGJ GdMQjQjIs - (3CHi eMeO ceGd GdOjf GdbGSe Hf GdbGSe Hf YeQ Hf efUhQ GdhGSWis; (3GdMQjQj,J (B516 (3g` s ((3GdMSf Hf GMSf Hf eMeO GdHNGQi GdNWjH s)
(3ChdgG (B:s
(3hHYO aEfi QCjJ GdebeGJ ef CaUM GdeUfaGJ HjGfkG hJgPjHkG hChVM GdeDdaGJ JHjGfkG hJQJjHkG s
(3BNQgG (B:s
(3hGdQhbH GdJi jYjT dgG cCfgG JQbH GdehJ ef hdOJ hGddg CYde Ke GdcJGH s
(3HChdgG Jedc SfI (B1177 (3g`s
(3eQJH Ydi MQha GdeYLes
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs